2019
DOI: 10.1371/journal.pmed.1002843
|View full text |Cite
|
Sign up to set email alerts
|

The Flooring for Injury Prevention (FLIP) Study of compliant flooring for the prevention of fall-related injuries in long-term care: A randomized trial

Abstract: Background Fall-related injuries exert an enormous health burden on older adults in long-term care (LTC). Softer landing surfaces, such as those provided by low-stiffness “compliant” flooring, may prevent fall-related injuries by decreasing the forces applied to the body during fall impact. Our primary objective was to assess the clinical effectiveness of compliant flooring at preventing serious fall-related injuries among LTC residents. Methods and findings The Floorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
105
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(106 citation statements)
references
References 32 publications
1
105
0
Order By: Relevance
“…Although previous studies did not specify whether they defined "fall direction" as the initial fall direction or landing configuration, our results for landing configuration are in agreement with those reported by Greenspan and colleagues, (13) who found that sideways falls had 5.7-fold higher odds for hip fracture than falls in other directions; by Nevitt and Cummings, (39) who reported that sideways or straight-down falls had 3.3-fold higher odds for fracture; and by Hwang and colleagues, (29) who found that, when compared to forward falls, both backward and sideways falls created over 10-fold higher risk for hip fracture. Future studies should separately consider and report outcomes for initial fall direction and landing direction.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although previous studies did not specify whether they defined "fall direction" as the initial fall direction or landing configuration, our results for landing configuration are in agreement with those reported by Greenspan and colleagues, (13) who found that sideways falls had 5.7-fold higher odds for hip fracture than falls in other directions; by Nevitt and Cummings, (39) who reported that sideways or straight-down falls had 3.3-fold higher odds for fracture; and by Hwang and colleagues, (29) who found that, when compared to forward falls, both backward and sideways falls created over 10-fold higher risk for hip fracture. Future studies should separately consider and report outcomes for initial fall direction and landing direction.…”
Section: Discussionsupporting
confidence: 91%
“…We previously reported that hand impact did not affect the risk for head impact during falls by residents of LTC. (22,33) Others have reported that arresting the fall with the hands associated with reduced risk for hip fracture among communitydwelling individuals, (14,39) but had no effect on hip fracture risk for older adults residing in nursing homes. (13) The discrepancy may be due to differences between LTC and community-based populations in factors such as upper limb strength and flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the exploration of fall prevention measures has attracted a large number of investigators. (11,12) Related research has also yielded many meaningful results, such as the progress of a series of fall assessment tools and the improvement of fall prevention measures for use in hospitals. (13)(14)(15)(16)(17)(18)(19) Correspondingly, the importance of interventions when falls occur and after falls are often overlooked.…”
Section: Introductionmentioning
confidence: 99%